European Union — Mexico: The Conclusion of a “New Generation” Trade Agreement - T. V. Sidorenko (Мир новой экономики)
The article analyses the main innovations of the modernised free trade agreement between the European Union and Mexico, signed in April 2018. The author examined such aspects of the agreement as the liberalisation of trade in food, telecommunications, financial services, as well as e-commerce, providing access to the market of government procurement, protection of intellectual property rights, investment facilitation and other. Members of the EU emphasised that the conclusion of a “new generation” trade agreement with Mexico is in line with the updated foreign economic strategy of this integration association, aimed at promoting the commercial interests of the European business outside the EU. They also argue that Mexico is a desirable market for the European companies, given the size of its economy, its population, and its membership in NAFTA. Therefore, the entry into force of the modernised agreement will allow the intensification of the trade and investment relations between the partners. The latter should provide an additional incentive for their economic development, especially for Mexico.